Addiction Competencies in the 2009 CACREP Clinical Mental Health Counseling Program Standards. Issue 1 (7th April 2013) - Lee, Tiffany K.; Craig, Stephen E.; Fetherson, Bianca T. L.; Simpson, C. Dennis
<x xml:space="preserve">Abstract</x> The Council for Accreditation of Counseling and Related Educational Programs developed addiction competencies for clinical mental health counseling students. This article highlights these competencies, provides an overview of current addiction training, and describes methods to integrate addiction education into curricula.